Precancerous and malignant diseases of the endometrium in patients with endometrial polyps in postmenopause - T. V. Klinyshkova; N. B. Frolova; E. A. Tsertsanova; N. P. Сhernyshova (Лечащий Врач, 2025)
Background. Benign proliferative processes of the endometrium are the cause of oncological risk, increased in the postmenopausal period. The clinical significance of endometrial polyps is determined by their prevalence in postmenopause and increased risk of precancerous and malignant lesions of the endometrium. Approaches to the management of patients with postmenopausal endometrial polyps are determined by the presence of symptoms, allowing for observation in asymptomatic cases. Additional studies are required to clarify the choice of active management tactics.Objective. The aim of the study was to examine the condition of the endometrium in patients with verified postmenopausal endometrial polyps.Material and methods. A retrospective cohort study was conducted at the gynecological department of the Private Healthcare Institution Clinical Hospital Russian Railways-Medicine of Omsk. The study cohort consisted of 133 women with postmenopausal endometrial polyps (mean age – 59.23 ± 6.34 years), who underwent hysteroresectoscopic polypectomy followed by histological examination of the endometrial polyps and surrounding endometrium.Results. The duration of postmenopause was 9.47 ± 6.66 years. Endometrial polyps dominated in women in late postmenopause (95% CI 60.4-76.4). Patients with postmenopausal endometrial polyps had an asymptomatic course (95% CI 61.2-77.2), uterine bleeding (95% CI 22.8-38.8), recurrent endometrial polyps (15.8%), concomitant treatment with tamoxifen (3.8%). According to the hysteroscopic examination data, a predominance of single endometrial polyps was established (95% CI 67.7-82.7), the sizes of which varied over a wide range (15.7 ± 9.4 mm). The prevalence of glandular-fibrous endometrial polyps (61.7%) over glandular endometrial polyps (36.8%) was characteristic. Atypical endometrial polyps was detected in two cases (1.5%), one of which had signs of malignancy (0.8%) against the background of uterine bleeding. The surrounding endometrium had signs of atrophy (61.7%) and cystic atrophy (34.6%). In 5 cases (3.8%), pathology of the surrounding endometrium was detected: simple endometrial hyperplasia without atypia, atypical endometrial hyperplasia, and endometrial adenocarcinoma. Signs of malignancy of atypical endometrial polyps and cancer in the surrounding endometrium were detected both in symptomatic (n = 41) and asymptomatic disease (n = 92) (p > 0.05).Conclusion. In patients with postmenopausal endometrial polyps, the disease occurs against the background of precancer and endometrial cancer localized in the polyp or surrounding endometrium in 3.8% of cases. The frequency of precancer and endometrial cancer against the background of a dominant asymptomatic course in postmenopause is 2.2%, which requires histological verification regardless of the size of the polyp according to the ultrasound examination data and the absence of clinical manifestations, and excludes the possibility of observational tactics.